Vitamin D Metabolism: Role in the Genesis of Diseases (International Journal of Medical and Surgical Sciences, 2016)
Vitamin D has traditionally been associated with bone metabolism, however it exerts different functions in various tissues of the body that possess the vitamin D (VCR) receptor and they are susceptible to its effect. Decreased vitamin D has also been associated with "nonclassical" diseases such as hypertension, metabolic syndrome, insulin resistance, diabetes, development of some cancers, lung disorders, autoimmunity and infertility, among others. Maternal vitamin D deficiency has been associated in the genesis of postnatal diseases. Further, many of these pathologies are produced by molecular alterations, mainly related to metabolism and receptor polymorphisms VCR. Vitamin D is considered a hormone, can be synthesized in the skin from 7-dehydrocholesterol by ultraviolet radiation B. The metabolism is complex and involves the interaction of several factors in its incorporation and final formation of calcitriol, the active form. To produce its effect requires activation of VDR receptor on the target cell, which activates specific gene sequences with different functions, through DNA promoter sequences in identified vitamin D response elements (VDRE). Many tissues have the VDR receptor and enzymes necessary for metabolism, so the spectrum of vitamin D action is very broad in the variety of pathologies produced. This review of vitamin D focuses primarily on the molecular aspects of its metabolism and its role in the genesis of "nonclassical", diseases, product of its reduction or alteration of metabolic diseases.